The Role of Parents in Enhancing Self-Esteem of School-Age Children: Exploring Parenting Styles, Involvement, and Socioeconomic Factors - Elshanum, Dira Carlissa (PELNUS | Pen en Light for Natural Union of Science, 2024)
This research investigates the critical role of parents in enhancing the self-esteem of school-age children. It explores the relationship between parenting styles, parental involvement, and children's self-worth, drawing on quantitative data from surveys and qualitative insights from interviews with parents and children. The findings reveal a significant correlation between authoritative parenting and higher self-esteem levels, emphasizing the importance of emotional support and positive reinforcement in shaping children's self-perception. Additionally, the study highlights the impact of parental involvement in educational settings, demonstrating that active engagement contributes positively to children's emotional development. Socioeconomic status was identified as a significant factor influencing self-esteem, with children from higher socioeconomic backgrounds reporting greater self-worth. The qualitative data provided deeper insights into the complexities of parenting dynamics, revealing the challenges parents face in balancing discipline and emotional support. The implications of these findings are multifaceted, offering practical recommendations for parents, educators, and policymakers to foster an environment that nurtures children's self-esteem. This research underscores the necessity of supportive parenting practices in promoting healthy emotional development, ultimately contributing to the well-being of future generations.